High resolution measurements of strain and tilt distributions in SiGe mesas using electron backscatter diffraction - Wilkinson, A (American Institute of Physics, 2006)
Electron backscatter diffraction allows the elastic strain and rotation tensors to be determined at high spatial resolution and with a strain sensitivity of ~10-4. The technique is used to investigate variations of strains and rotations near the surface of 200 nm thick epitaxial layers of Si0.85Ge0.15 grown on a Si substrate patterned with mesa stripes. In wide mesa stripes the strain relaxation and lattice curvature are confined to the outer edges of the mesa. While in narrower mesas the relaxation extends across the entire mesa width. Measured stress levels confirm earlier predictions of the extent of relaxation with mesa width.